Analisis Forensik Kasus Pembacokan: Studi Kasus di RSUD Langsa - Ardivan, Marcel; Safira, Safira; Rabbi, Athaya; Hazira, Hazira; Putri, Armelia; Herawati, Netty (Innovative: Journal Of Social Science Research, 2025)
Indonesia, as a state governed by law, upholds the supremacy of legal justice, particularly in addressing criminal acts such as homicide. One prevalent form of crime against life is violence involving sharp objects, often resulting in stab or incised wounds to vital body parts such as the neck. This study employs a case report method and library research to examine the legal and medicolegal aspects of a murder case involving sharp force trauma. The analyzed case involves a male victim with severe open wounds on the neck, head, and arm caused by a sharp weapon. Postmortem examination revealed that the cause of death was massive bleeding due to the severance of major blood vessels in the neck. From a medicolegal perspective, the incident qualifies as a criminal offense under Article 338 of the Indonesian Criminal Code, which addresses homicide. This study highlights the critical role of forensic medicine in determining the cause of death and providing scientific evidence to support the legal process.